2018
DOI: 10.2478/jtim-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Aplastic anemia in China

Abstract: Aplastic anemia (AA) is a hematologic disease characterized by pancytopenia. Up to now, severe aplastic anemia (SAA) has been recognized by international and domestic scholars as an autoimmune disease with bone marrow (BM) failure mediated by the hyperfunctional T lymphocytes. The incidence of AA is more in China compared with other countries. In the recent years, both the pathogenesis and treatment of AA have made a great progress in our country. Thus, the therapeutic effect of AA was much better than before.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In the course of exploring the pathogenesis of SAA, it was found that the number of mDCs in SAA patients was significantly higher than that of normal people, and the ratio of mDC/pDC was significantly increased (15)(16)(17)(18). The expression of costimulatory molecule CD86 on the surface of mDCs was significantly increased (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of exploring the pathogenesis of SAA, it was found that the number of mDCs in SAA patients was significantly higher than that of normal people, and the ratio of mDC/pDC was significantly increased (15)(16)(17)(18). The expression of costimulatory molecule CD86 on the surface of mDCs was significantly increased (5).…”
Section: Discussionmentioning
confidence: 99%
“…The number of new cases of HBP cancer worldwide in 2018 was approximately 1.85 million, accounting for 10% of all newly diagnosed cancer cases and resulting in a great financial burden[ 4 , 5 ]. Due to the large number of HBP cancer cases, from the perspective of prevention[ 6 , 7 ], identifying high-risk populations has become an urgent public health issue[ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the etiology and pathogenesis of SAA have remained to be fully elucidated. Previous studies by our group have confirmed that various immune cells and cytokines constitute an abnormal immune status in patients with SAA (20,21), including the involvement of Th1/Th2 subset imbalances, hyperfunctional CTLs, insufficiencies in the regulatory T and NK cell populations and negative hematopoietic cytokines (22,23). These subsequently induce excessive apoptosis of CD34 + HSCs and inhibit hematopoietic colony formation through the perforin, granzyme B, Fas/FasL and the TNF-related apoptosis-inducing ligand pathways (13).…”
Section: Discussionmentioning
confidence: 72%
“…No statistically significant difference in the expression of LILRA3 was obtained between SAA patients with short-term remission (≤12 months) and long-term remission (>12 months). A significant risk of relapse was reported with rapid tapering of cyclosporine in patients with remission SAA and the treatment should be continued for a long time until the immunoreaction is completely back to normal ( 20 ). LILRA3 upregulated the transcription of IL-1A, IL-1B and IL-6 and modulated the expression of co-stimulatory molecules and MHC in B-cells and monocytes.…”
Section: Discussionmentioning
confidence: 99%